2021
DOI: 10.36908/isbank.v6i2.127
|View full text |Cite
|
Sign up to set email alerts
|

ANALISIS PENINGKATAN KESEJAHTERAAN NASABAH TERHADAP PEMBIAYAAN MURABAHAH (Studi Kasus Bank Aceh Syariah Capem Krueng Geukueh)

Abstract: This study aims to determine differences in income before and after getting murabaha financing at Bank Aceh Syariah Capem Krueng Geukueh. The research method uses quantitative methods with a sample of 45 respondents. Data collection was carried out using a Likert scale questionnaire. Based on the results of the study there is a relationship between welfare and cheap financing at Bank Aceh Syariah Capem Krueng Geukeuh, with the difference in the difference in average income before and after amounting to -8,587 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
2
1
Order By: Relevance
“…The results of this study also showed that BMT financing did not affect its members' welfare improvement who came from micro-enterprises in the Purworejo traditional markets. These results are inconsistent with research by Nizar (2016), Alexandi Asy Syahidah (2018), Atika (2018), Fasilyana et al (2019), Damanhur and Utami (2020), Ferdiansyah et al (2021), Mahdalena et al (2021).…”
Section: Figure 2 Factor Loading Of Convergent Validity Testcontrasting
confidence: 63%
See 2 more Smart Citations
“…The results of this study also showed that BMT financing did not affect its members' welfare improvement who came from micro-enterprises in the Purworejo traditional markets. These results are inconsistent with research by Nizar (2016), Alexandi Asy Syahidah (2018), Atika (2018), Fasilyana et al (2019), Damanhur and Utami (2020), Ferdiansyah et al (2021), Mahdalena et al (2021).…”
Section: Figure 2 Factor Loading Of Convergent Validity Testcontrasting
confidence: 63%
“…The research results by Fasilyana et al (2019) showed that financing significantly affected the business development of its members. Likewise, financing had a significant positive effect on improving the welfare of its members (Nizar, 2016;Alexandi & Asy Syahidah, 2018;Atika, 2018;Fasilyana et al, 2019;Damanhur & Utami, 2020;Ferdiansyah et al, 2021;Mahdalena et al, 2021). However, research by Prastiawati and Darma (2016) revealed that BMT financing did not significantly affect the business development and welfare improvement of traditional market traders (with the object being traditional market traders in Bantul).…”
Section: Darma and Handoyomentioning
confidence: 99%
See 1 more Smart Citation